2021
DOI: 10.1038/s41598-021-92265-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rs2414096 polymorphism of CYP19 gene on susceptibility of polycystic ovary syndrome and hyperandrogenism in Kashmiri women

Abstract: Polycystic ovary syndrome (PCOS) is the most common reproductive endocrine disorder in pre-menopausal women having complex pathophysiology. Several candidate genes have been shown to have association with PCOS. CYP19 gene encodes a key steroidogenic enzyme involved in conversion of androgens into estrogens. Previous studies have reported contradictory results with regard to association of SNP rs2414096 in CYP19 gene with PCOS and hyperandrogenism in different ethnic populations. Present study was aimed to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Increased LH/FSH can induce androgen level and reduces the expression of estrogen, while increased androgen and decreased estrogen, in turn, aggravate LH/FSH via failure of dominant follicles, causing a vicious cycle. Also, PCOS women of the GG genotype had higher plasma insulin and HOMA-IR which was consistent with a study among the Kashmiri population, and findings by Sowers and colleagues, who had concluded a positive association of rs2414096 SNP of the CYP19 gene with hyperandrogenism in PCOS women [ 11 , 27 ]. The estradiol levels in PCOS and controls were not significantly different between the three genotypes.…”
Section: Discussionsupporting
confidence: 90%
“…Increased LH/FSH can induce androgen level and reduces the expression of estrogen, while increased androgen and decreased estrogen, in turn, aggravate LH/FSH via failure of dominant follicles, causing a vicious cycle. Also, PCOS women of the GG genotype had higher plasma insulin and HOMA-IR which was consistent with a study among the Kashmiri population, and findings by Sowers and colleagues, who had concluded a positive association of rs2414096 SNP of the CYP19 gene with hyperandrogenism in PCOS women [ 11 , 27 ]. The estradiol levels in PCOS and controls were not significantly different between the three genotypes.…”
Section: Discussionsupporting
confidence: 90%
“…Ashraf et al reported a SNP (rs2414096) of the CYP19 gene to be associated the PCOS susceptibility and hyperandrogenism in patients from Kashmir, India [62].…”
Section: Cyp19 (Cytochrome P450 Family 19) Genementioning
confidence: 99%
“…In this regard, polymorphisms in CYP11A, CYP17, CYP19 and CYP21 genes are related to the alteration in the steroidogenesis with an overproduction of androgen hormones [ 45 ]. Recent studies have demonstrated that CYP 17 5’-UTR MspA1 (rs743572) and CYP 19 (rs2414096) polymorphisms increase the susceptibility to develop PCOS in young women, altering different hormone genesis pathways [ 46 , 47 , 48 ].…”
Section: Mechanisms Involved In Pcos Pathogenesismentioning
confidence: 99%